Securitisation of the response to rhinoceros poaching in South Africa - Biegus, Olga (Department of Public Law, 2019)
The thesis examines conditions and nature of securitisation of a rhinoceros antipoaching response in South Africa after 2010. In a surge of rising numbers of animals being illegally hunt for their horns and other parts, the country awoke in a scramble over effective mitigation measures. Through lenses of securitisation theory, I analyse historical and social contexts, that led a range of state and nonstate actors in framing rhinoceros poaching as an emergency and helped in proclaiming it a national security threat. Aimed to secure the survival of rhinoceros in South Africa and beyond, the securitisation was achieved through chain of practices that have been introduced over the last decade in the country. Applying sociological understanding of the theory that draws on Bourdieu’s concept of the field and Foucauldian elements of theory of governmentality, I focus on evolving character of such practices, which effected in a securitised response to poaching. According to this approach, actors and audience inclined in power relations produce new meanings and practices that aim to eliminate, the threat. They do so by applying extraordinary measures, such as creating new policies or drawing attention and resources to the pronounced threat. I argue that international actors initiated the security framing of broader wildlife crime issues, which South Africa eventually accepted and reinforced as a dominant narrative. Aligning with the global actors was possible because of the historical security-based politics and aimed to achieve more favourable image of country’s tourism industry and attract financial support. On the other hand, donors help did not come without interests. These were linked to Western -oriented concepts of nature and wildlife conservation reoriented by security discourse. By using national security as a justification for extraordinary measures, such as delegating anti-poaching agenda to the security cluster and allocating more funds, South Africa was able to gain more control over resources rich areas though applying wildlife security narrative. The research utilises information from South African government agencies, nongovernmental organisation as well as other actors engaged in broadly understood conservation topic within last decade. By analysing laws, strategies, policies, official briefings, independent and academic reports as well as media articles, I construct a timeline of practices that led to securitising the rhinoceros antipoaching strategies. The thesis comprises of review of the existing literature on security and securitisation studies as well as critical analysis of trends global environmental politics, followed by specific theoretical approach and methodology that allows to analyse key elements. The research concludes with identifying potential risks and opportunities of securitisation, depending on development scenarios and provides the list of recommendations to mitigate potential negative impacts.